VALIDITY OF LEARNING TOOLS CREATIVE PROBLEM SOLVING MODELS TO IMPROVE STUDENTS' PHYSICS PROBLEM-SOLVING ABILITY - Cahya, Ratna; Rokhmat, Joni; Gunada , I Wayan (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to produce a product in the form of a suitable Creative Problem Solving learning device to improve student's ability to solve physics problems. This research is a research development or Research & Development (R&D) that uses a 4D model research design consisting of the Define, Design, Develop, and Disseminate stages. The products produced are Learning Implementation Plans, Student Worksheets, and physics problem-solving ability test instruments. The product validity test was obtained through validation by 3 expert validators, namely physics education lecturers and 3 practitioner validators, namely physics teachers. The average value obtained is 3.39 to 3.67 with very valid criteria. Based on the results of the average value of the validity test, it shows that the Creative Problem Solving model of physics learning device is suitable for use in learning.